Designing Interest and Tax Penalty Regimes - Waerzeggers, Christophe (Tax Law Technical Note; Tax Law Technical Note ;, 2019)
Nearly all tax systems have some form of interest and tax penalty regimes. Interest payable on any late or underpayment of tax seeks to protect the present value of the tax amount to the government budget, whereas penalties are intended to deter taxpayers from defaulting on their tax obligations-and to punish them if they do-to achieve horizontal equity vis-a-vis compliant taxpayers. As interest and penalties serve very different objectives, they should not be applied in a mutually exclusive manner. This Tax Law IMF Technical Note focuses on the key issues that should be taken into consideration in designing interest and penalty regimes in tax legislations.